Pengembangan E-Comic Berbasis Pendidikan Karakter dan High Order Thinking Skills (HOTS) Untuk Meningkatkan Kemampuan Literasi - Firiyanti, Ilma; Hamidah, Alisa; Widodo, Ari; Maghfiroh, Lailatul; Susanti, Nevi; Ashirotun Ni'ma, Rosida; Mashfufah, Aynin (UNIB Press, 2024)
Poor reading comprehension is still a significant issue, particularly for primary school pupils. To enhance student literacy, we need innovative approaches that leverage scientific and technological advancements. The goal of this project is to create and manufacture e-comic goods as a scientific and science-related learning innovation. This research approach makes use of Borg & Gall development research (R&D), whose phases align with the requirements of product development. Experts' and students' tests of the product's viability have shown encouraging findings. The findings of the validation of e-comic products based on HOTS and character education show that they are extremely practicable to use, with media experts indicating 94.00% feasibility and material experts indicating 89.00%. Eighty-five percent of teacher practitioners completed the evaluation. 92.00% was the outcome of the student answer. According to this research, e-comics that are based on HOTS and character education are highly practical and efficient to use, which means that they may be developed as learning innovations in the future.